Madagascar Public Expenditure Review : Implementation of the Madagascar Action Plan, Analysis for Results, Executive Summary - World Bank (Washington, DC, 2012)
The primary objective of this Public Expenditure Review is to analyze the macro-economic underpinnings of the Madagascar Action Plan (MAP), to review if the existing procedural and institutional framework for the generation and the use of public resources facilitates MAP implementation, and to provide guidance and recommendations for effective and successful implementation of the new development strategy. This report, which follows the one published in 2005 for the 1997-2005 periods, is part of a series of programmatic reviews agreed upon with the Government of Madagascar. It differs from typical expenditure reviews as it was prepared in close collaboration and partnership with the Malagasy administration and represents the joint efforts of a multidisciplinary team. This Public Expenditure Review consists of five volumes: the first volume being the executive summary and the second provides a global analysis of the environment within which the MAP will be implemented. Three other volumes deal with the health, nutrition and water and sanitation sectors.